PENGARUH KARAKTERISTIK DEMOGRAFI, MASA KERJA DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KOMITMEN AFEKTIF DI PT. BENSATRA ADVERTISING MEDAN - Indra, Aulia (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
From the initial research that researchers do, the phenomenon that occurs in the company is the number of employees who relaxed when the work is still loose, the experts in the company feel comfortable because of the absence of rivals, as well as lack of trust given the company to employees in providing jobs in scale the greater one. This is behind the lack of affective commitment of employees to the company. The purpose of this study is to determine the influence of demographic characteristics, length of work and perceived organizational support to affective commitment at PT. Bensatra Advertising Medan. The analysis technique used is multiple linear regression. The results showed that simultaneously variable of demography characteristic, work period and perceived organizational support have significant effect to affective commitment. Demographic characteristics have no significant effect on affective commitment, tenure and perceived organizational support affect affective commitment.